Water balance and acute mountain sickness before and after arrival at high altitude: 4,350 m - Westerterp, Klaas R.; Robach, Paul; Wouters, Loek; Richalet, Jean-Paul (Acta Andina, 2025)
The present study is a first attempt to measure water balance and its components at altitude, using labeled water and bromide dilution, and relating the results with acute mountain sickness (AMS). Water intake, total water output and water output in urine and feces were measured over a 4-day interval before and a subsequent 4-day interval after transport to 4,350 m. Total body water and extracellular water were measured at the start and at the end of the two intervals. There was a close relationship between energy intake and water intake and the relation was unchanged by the altitude intervention. Subjects developing AMS reduced energy intake and water intake correspondingly. The increase in TBW in subjects developing AMS was accompanied by a reduction in total water loss. They did not show the increased urine output, compensating for the reduced evaporative water loss at altitude. Subjects showed a significant increase in TBW after 4 days at altitude. Subjects with AMS showed the biggest shifts in ECW relative to TBW. In conclusion, fluid retention in relation to AMS is independent of a change in water requirements due to altitude exposure. Subjects developing AMS were those showing a fluid shift of at least 11 from the intracellular to the extracellular compartment or from the extracellular to the intracellular compartment.